TRANSFORMING ISLAMIC EDUCATION THROUGH DIGITAL INNOVATION: A REVIEW OF INTERACTIVE LEARNING APPROACHES - Agus Fawait; Al-Amin (Adisam Publisher, 2026)
This study examines the transformation of Islamic education through digital innovation by reviewing various interactive learning approaches implemented in contemporary educational environments. The rapid advancement of digital technology has significantly influenced teaching and learning processes in Islamic education, encouraging educational institutions to adopt more interactive, flexible, and technology-based instructional models. This study aims to analyze the role of digital innovation in improving students’ conceptual understanding and spiritual development within Islamic education. The research employed a qualitative library research method by collecting and analyzing scholarly articles, books, conference proceedings, and reputable international journal publications indexed in Scopus from the last five years. The data were analyzed using content analysis techniques to identify major trends, challenges, and opportunities related to digital transformation in Islamic education. The findings indicate that interactive digital learning approaches such as e-learning, gamification, multimedia learning, virtual classrooms, and artificial intelligence-based educational systems significantly improve student engagement, motivation, and conceptual understanding. Furthermore, digital technologies provide broader access to Islamic educational resources and support personalized learning experiences. However, the study also reveals several challenges, including limited digital competencies among educators, inadequate technological infrastructure, and insufficient integration of spiritual and ethical values within digital learning environments. This study highlights that successful digital transformation in Islamic education requires a balanced integration between technological innovation and Islamic spiritual principles. Therefore, Islamic educational institutions need to develop holistic and value-oriented digital pedagogical models to ensure that technological advancement contributes not only to academic achievement but also to moral and spiritual development. This study contributes to the literature by providing a comprehensive review of interactive digital learning approaches and their implications for the future development of Islamic education in the digital era.